Unicondylar knee retrieval analysis. - Manson TT; Kelly NH; Lipman JD; Wright TM; Westrich GH (The Journal of arthroplasty, 2010)
Unicondylar knee arthroplasty (UKA) is considered an alternative to total knee arthroplasty for patients who have arthritis limited to one compartment of the knee. This study examined surface damage of 3 contemporary UKA designs that were retrieved at revision surgery. Two of the UKA designs were fixed bearing and one was mobile bearing. Demographic information was collected, as well as information about the implants used at revision surgery. Articular surface damage was greater in the fixed-bearing designs as compared to the mobile bearing, although the mobile-bearing implants had significantly shorter length of implantation. Backside damage was also graded for the mobile bearing and when combined with articular wear resulted in overall damage scores higher than both fixed-bearing designs. The fixed-bearing designs showed delamination and surface deformation, whereas the mobile bearing had no evidence of these damage modes. However, mobile-bearing components showed other types of wear, and significant wear damage was present on the bearing surfaces of the mobile-bearing implants despite a short time of implantation. At the time of conversion to a total knee arthroplasty, more than 50% of cases required the use of stems, augments, or constrained inserts for the tibial reconstruction. In conclusion, wear modes differed among UKA prosthesis designs. Revision of a UKA to a total knee arthroplasty remains complex with the tibial preparation more complicated than in the primary setting.